Kondo physics in transport through a quantum dot with Luttinger-liquid leads - Andergassen, Sabine; Enss, Tilman; Meden, Volker (Physical review. B, Condensed matter and materials physics, 2006)
We study the gate voltage dependence of the linear conductance through a quantum dot coupled to one-dimensional leads. For interacting dot electrons but noninteracting leads Kondo physics implies broad plateaulike resonances. In the opposite case Luttinger-liquid behavior leads to sharp resonances. In the presence of Kondo as well as Luttinger-liquid physics and for experimentally relevant parameters, we find a line shape that resembles the one of the Kondo case.